The Effect of the EU‐Brand on Citizens' Trust in Policies: Replicating an Experiment. (5th May 2021) - Eshuis, Jasper; van de Geest, Thijs; Klijn, Erik Hans; Voets, Joris; Florek, Magdalena; George, Bert
Abstract: Karens et al. (2016) conducted an experiment to measure the effect of the European Union (EU) brand on citizens' trust in policies. Experiments conducted with economics students in Belgium, Poland, and The Netherlands showed a consistently positive and significant effect of applying the EU brand, on trust in the policies. This study presents seven replications conducted several years after Karens et al.'s experiments. The replications show no significant effects of the EU brand on trust in policies. These findings demonstrate that brand effects may vary over time. To identify a population effect size across all experiments, a meta‐analysis was conducted. The meta‐analysis shows that—overall—the EU‐brand has a small but significant positive effect on citizens' trust in policies. The article tests earlier findings, and discusses intricacies of conducting replications. It elaborates explanations for the results in the replications, and the replication problems with experiments based on evaluative conditioning.